2022
DOI: 10.3390/biom12081030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Subcellular, and Arrhythmogenic Mechanisms in Genetic RyR2 Disease

Abstract: The ryanodine receptor (RyR2) has a critical role in controlling Ca2+ release from the sarcoplasmic reticulum (SR) throughout the cardiac cycle. RyR2 protein has multiple functional domains with specific roles, and four of these RyR2 protomers are required to form the quaternary structure that comprises the functional channel. Numerous mutations in the gene encoding RyR2 protein have been identified and many are linked to a wide spectrum of arrhythmic heart disease. Gain of function mutations (GoF) result in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 137 publications
0
12
0
Order By: Relevance
“…Numerous RyR1 and RyR2 mutations associated with MH and CPVT, respectively, have been functionally characterized with the vast majority resulting in gain-of-function channels ( Hernandez-Ochoa et al, 2016 ; Fowler and Zissimopoulos, 2022 ). However, how pathogenic RyR mutations function at the molecular or structural level, i.e., what is the defective RyR regulatory mechanism(s), is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous RyR1 and RyR2 mutations associated with MH and CPVT, respectively, have been functionally characterized with the vast majority resulting in gain-of-function channels ( Hernandez-Ochoa et al, 2016 ; Fowler and Zissimopoulos, 2022 ). However, how pathogenic RyR mutations function at the molecular or structural level, i.e., what is the defective RyR regulatory mechanism(s), is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal SR Ca 2+ release due to missense mutations in RYR1 and RYR2 results in neuromuscular (e.g., malignant hyperthermia, MH) and cardiac disease (e.g., catecholaminergic polymorphic ventricular tachycardia, CPVT), respectively ( Hernandez-Ochoa et al, 2016 ; Fowler and Zissimopoulos, 2022 ). Mutations are found throughout the RyR peptide sequence, but tend to concentrate on five structural domains, namely, the N-terminus domain (NTD), bridging solenoid B, core solenoid, transmembrane domain and C-terminus domain ( Fowler and Zissimopoulos, 2022 ). Neighboring NTDs from the four RyR subunits interact with each other to promote channel closure ( Tung et al, 2010 ; Zissimopoulos et al, 2013 ; Zissimopoulos et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free experiments have indicated that a vast majority of tested CVPT1 mutations activate the RyR2 channel in response to elevated luminal Ca 2+ [ 181 , 182 , 183 , 184 ]. Although hypersensitivity to cytosolic Ca 2+ and hyposensitivity to cytosolic Mg 2+ could also participate [ 112 , 185 , 186 , 187 , 188 ], more frequent spontaneous Ca 2+ release under conditions of store Ca 2+ overload (SOICR) represents a common defect caused by CPVT1 mutations (comprehensively reviewed in [ 75 , 189 , 190 ]. This inappropriate RyR2 activation results in diastolic SR Ca 2+ leak, which has been suggested to trigger fatal cardiac arrhythmias [ 191 ].…”
Section: The Ryr2 Channel As An Endogenous Target Of Dantrolenementioning
confidence: 99%
“…When using Schrodinger's Prime protein-protein docking software, the more negative the binding energy, the better the fit. The most thermodynamically favored site of interaction (site 1: brown) for HIV-Tat resides in the region within the junctional solenoid region (JSOL: amino acids (AA) 1702-1963) [56,57], with 14 hydrogen bonding, 3 salt bridges, and 1 pi stack (See Table 1). Note, the numbering of the AA for HIV-Tat that is listed is derived from the crystal structure provided by Protein Data Bank (PDB id; 1TIV).…”
Section: In Silico Molecular Docking Of Hiv-tat On Ryr2mentioning
confidence: 99%